Neuronal intranuclear inclusion disease is genetically heterogeneous. Issue 9 (10th August 2020) - Chen, Zhongbo; Yan Yau, Wai; Jaunmuktane, Zane; Tucci, Arianna; Sivakumar, Prasanth; Gagliano Taliun, Sarah A.; Turner, Chris; Efthymiou, Stephanie; Ibáñez, Kristina; Sullivan, Roisin; Bibi, Farah; Athanasiou‐Fragkouli, Alkyoni; et al.
Abstract: Neuronal intranuclear inclusion disease (NIID) is a clinically heterogeneous neurodegenerative condition characterized by pathological intranuclear eosinophilic inclusions. A CGG repeat expansion in NOTCH2NLC was recently identified to be associated with NIID in patients of Japanese descent. We screened pathologically confirmed European NIID, cases of neurodegenerative disease with intranuclear inclusions and applied in silico‐based screening using whole‐genome sequencing data from 20 536 participants in the 100 000 Genomes Project. We identified a single European case harbouring the pathogenic repeat expansion with a distinct haplotype structure. Thus, we propose new diagnostic criteria as European NIID represents a distinct disease entity from East Asian cases.